Can compassion provide a lifeline for navigating Coronavirus (COVID-19) in higher education?. (3rd July 2021) - Parfitt, Anne; Read, Stuart; Bush, Tanvir
ABSTRACT: The Coronavirus pandemic has caused considerable challenges for the higher education sector, leaving many students and staff to experience a sense of liminality as they cope with these challenges. This article, written by three disabled academics based in the UK, reports how during the Coronavirus pandemic, compassion and compassionate spaces could be nurtured when students and staff took the opportunity to recognise their common existence. We share insights from focus groups held with seven disabled academics and learners on their encounters with the pandemic, such as managing the complexities of studying and working from home. We demonstrate that acknowledging and responding compassionately to feelings of vulnerability can offer a lifeline for individuals. Specifically, we propose the application of the social model of disability when seeking to embed compassion in the neoliberal academy. By so doing, the higher education sector can benefit in terms of navigating our extraordinary Coronavirus circumstances, and in building a future inclusive post-pandemic academy.